Discovery of Kribiodorum Kieffer (Diptera: Chironomidae) in the Neotropical region: a new species from Brazilian Amazon rainforest - Dantas, Galileu P.s.; Hamada, Neusa (Zootaxa, 2021)
Kribiodorum is a small genus of non-biting midges, currently composed of only five nominal species, one Nearctic, two African and two Oriental. The objective of this study is to provide the first report of this genus to the Neotropical region and to describe a new species, based on male and female from southern Amazonas state, Brazil. Kribiodorum amazonicum sp. n. is easily distinguished from the congeneric species by the color pattern of the wings and legs and by the morphology of the genitalia.